Cybersecurity essentials - Brooks, Charles J.; Grow, Christopher; Craig, Philip; Short, Donald (Sybex, 2017)
An accessible introduction to cybersecurity concepts and practices, 'Cybersecurity Essentials' provides a comprehensive introduction to the field, with expert coverage of essential topics required for entry-level cybersecurity certifications. An accessible introduction to cybersecurity concepts and practicesCybersecurity Essentials provides a comprehensive introduction to the field, with expert coverage of essential topics required for entry-level cybersecurity certifications. An effective defense consists of four distinct challenges: securing the infrastructure, securing devices, securing local networks, and securing the perimeter. Overcoming these challenges requires a detailed understanding of the concepts and practices within each realm. This book covers each challenge individually for greater depth of information, with real-world scenarios that show what vulnerabilities look like in everyday computing scenarios. Each part concludes with a summary of key concepts, review questions, and hands-on exercises, allowing you to test your understanding while exercising your new critical skills. Cybersecurity jobs range from basic configuration to advanced systems analysis and defense assessment. This book provides the foundational information you need to understand the basics of the field, identify your place within it, and start down the security certification path. Learn security and surveillance fundamentals Secure and protect remote access and devices Understand network topologies, protocols, and strategies Identify threats and mount an effective defenseCybersecurity Essentials gives you the building blocks for an entry level security certification and provides a foundation of cybersecurity knowledge.- Resumé vydavatel
Keywords: kybernetická bezpečnost; počítačová bezpečnost; informační bezpečnost; cyber security; computer security; information security; elektronické knihy; kolektivní monografie; electronic books; collective monographs